THE ROLE OF TECHNOLOGY IN SCHOOL RESOURCE MANAGEMENT: A STUDY ON PUBLIC ELEMENTARY SCHOOLS IN MADAGASCAR - Eric, Ralainirina Razokiny; Arrive, Jean Tsitaire; Emynorane, Ralaivao Hanginiaina; Bien-Aimé, Whega Danitsaike (Program Studi PGSD, FKIP, Universitas Mataram, 2025)
This study investigates the role of technology in school resource management in public elementary schools in Madagascar. The study adopts a qualitative research methodology, utilizing observation, interviews, and documentation as primary data collection techniques. The key informants for this study are 10 school principals from various public elementary schools across Madagascar, selected based on their experience and administrative roles. The findings of this study highlight three critical aspects: first, technology plays a significant role in enhancing school management efficiency, allowing for better planning, communication, and monitoring of school resources. Second, it contributes to the improvement of school archives, with digital records providing easy access, security, and long-term preservation of important school documents. Finally, the study reveals several challenges to technology adoption, including limited digital literacy among staff, inadequate infrastructure, and financial constraints that hinder the full integration of technology in resource management. The study concludes by recommending targeted training programs for school staff, enhanced funding for technological infrastructure, and the development of a clear digital resource management policy tailored to the needs of public elementary schools in Madagascar.